2019
DOI: 10.18502/ijhoscr.v13i3.1276
|View full text |Cite
|
Sign up to set email alerts
|

Is There Any Correlation between Migraine Attacks and Iron Deficiency Anemia? ACase-Control Study

Abstract: Background: Migraine headache is an episodic abnormality which usually presents with a severe headache, accompanied by nausea, photo and sound sensitivity, and autonomic symptoms. Iron accumulation in brain, especially peri-aqueductal grey is associated with duration of the disease, and apparently there is an association between body iron storage status and the incidence of migraine; hence, the present study was conducted to investigate the plausible association between iron-deficiency anemia and migraine in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 27 publications
2
21
0
Order By: Relevance
“…In our search, we also found a case-control study intended to build further upon the hypothesized role of iron in migraine, which plays an essential role in the synthesis of serotonin, dopamine and norepinephrine (96). Accumulation of iron in the brain, specifically in the deep brain nuclei and the periaqueductal gray matter, has been shown to be related to the migraine neurobiology -supported by earlier neuroimaging evidence (97)(98)(99)(100).…”
Section: Additional Topicsmentioning
confidence: 81%
See 1 more Smart Citation
“…In our search, we also found a case-control study intended to build further upon the hypothesized role of iron in migraine, which plays an essential role in the synthesis of serotonin, dopamine and norepinephrine (96). Accumulation of iron in the brain, specifically in the deep brain nuclei and the periaqueductal gray matter, has been shown to be related to the migraine neurobiology -supported by earlier neuroimaging evidence (97)(98)(99)(100).…”
Section: Additional Topicsmentioning
confidence: 81%
“…These findings suggest that treatment for iron-deficiency anemia or iron supplementation might be a beneficial preventive method for patients suffering from migraine coinciding with iron deficiency anemia. Indeed, both migraine and iron-deficiency (induced by heavy menstrual flow) are more common in young females (96).…”
Section: Additional Topicsmentioning
confidence: 99%
“…This results in hypochromic microcytic anemia, especially in the 2nd and 3rd trimester, which may give adverse symptoms of organ and tissue dysfunction [106]. Premature birth or a low weight birth may occur [107], as well as myocardial hypoxia (e.g., tachycardia) [108], cerebral hypoxia (e.g., weakness, drowsiness, headaches, and dizziness) [109][110][111], immunosuppression [111], and appetite disorders (e.g., eating chalk) [112]. The prevalence of anemia in pregnant women ranges from 17% to 31% in Europe and North America, 53-61% in Africa, and 44-53% in Southeast Asia [113].…”
Section: Iron (Fe)mentioning
confidence: 99%
“…Patients with iron-deficiency anemia had a high frequency of migraine ( 15 ). A case-control study found that female migraineurs had low serum ferritin levels ( 17 ). However, the case-control study did not perform further age-stratified analysis, which was different from our study.…”
Section: Discussionmentioning
confidence: 99%
“…Ferritin, an important biomarker of body iron stores ( 16 ), deserves attention for its relationship with migraines. An observational study found lower serum ferritin levels in woman migraineurs ( 17 ), suggesting a role for dietary iron intake in the management of migraine. Dopamine plays a role in the pathogenesis of migraine, and iron is an essential trace element for the synthesis of dopamine ( 18 20 ).…”
Section: Introductionmentioning
confidence: 99%